Bionic man: Principles and limits - Roumeliotis, George (Ηθική. Περιοδικό φιλοσοφίας, 2021)
The subject of this paper is the ethical considerations raised in the issue of “bionic man”, a man whose many organs have been replaced by artificial, and the principles and ethical limitations that are inherent in this process. Four basic bioethical principles are acknowledged in the international bibliography: a) the principle of beneficence; b) the principle of autonomy and informed consent of patients; c) the principle of justice; d) the principle of equality. Apart from this, some more issues should be taken into consideration in the discussion about the ethics of artificial implants: the allocation of health care and economic resources, the patentability of implants, the use of implants in the human consciousness itself and the subsequent changes of implants in one’s personality, as well as the willingness of a patient to accept an implant under the prism of his/her belonging to a specific subculture, due to his/her impairment.